Legal Protection for Children Victim of Bullying Which Causing Mental Health Disorder - Try Ahmad Mirza; Nandang Sambas; Caecielia w. (SOEPRA, 2020)
Abstract: Bullying has become a concerning phenomenon in any part of the world. Bullying of children has a serious impact, victims can experience psychosomatic when going to school, feel worthless, feel alienated, depressed, even commit suicide. This study discusses how the legal protection for children victim of bullying which causing mental health disorder is reviewed based on Law Number 35 the Year 2014 Regarding Child Protection and Law Number 18 the Year 2014 Regarding Mental Health and is associated with the implementation of child protection in the Social Service for Women's Empowerment and Child Protection in Cirebon City and prevention of mental health disorders in one of the hospitals in West Java. Based on the results of the study it can be concluded that children victim of bullying who had mental health disorders receive special protection as victims of psychological and physical violence (bullying) and special protection for children with disabilities who are also included in the term of People With Mental Disorder in the terminology of mental health. Legal protection also includes promotive and preventive efforts to prevent bullying children from falling into mental health disorders as well as curative and rehabilitative conditions for children who had experienced mental health disorders. All the efforts are carried out by the Government, Regional Government, Community, Family, and Parents. Integration of all components of this legal protection is expected to reduce the incidence of bullying against children and also be able to suppress mental health disorders as an outcome.Keywords: Legal protection of children, Bullying, Mental Health Disorder Abstrak: Bullying menjadi fenomena yang sangat memprihatinkan di belahan dunia manapun Bullying terhadap anak membawa dampak yang serius, korban dapat mengalami psikosomatis ketika akan berangkat sekolah, merasa tidak berharga, merasa terasingkan, depresi hingga melakukan bunuh diri. Penelitian ini membahas bagaimana Perlindungan Hukum bagi Anak Korban Bullying yang Mengakibatkan Gangguan Kesehatan Jiwa dikaji berdasarkan Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak dan Undang-Undang Nomor 18 Tahun 2014 Tentang Kesehatan Jiwa serta dikaitkan dengan pelaksanaan perlindungan anak di Dinas Sosial Pemberdayaan Perempuan dan Perlindungan Anak (DSPPPA) Kota Cirebon dan penanggulangan gangguan kesehatan jiwa di salah satu Rumah Sakit di Jawa Barat. Berdasarkan hasil penelitian dapat disimpulkan bahwa Anak Korban Bullying yang Mengalami Gangguan Kesehatan Jiwa mendapat perlindungan khusus sebagai korban kekerasan psikis dan fisik (bullying) serta perlindungan khusus anak penyandang disabilitas yang juga termasuk dalam istilah ODGJ (Orang Dengan Gangguan Jiwa) dalam terminologi Kesehatan Jiwa. Perlindungan hukum tersebut mencakup upaya promotif dan preventif untuk menghindari anak korban bullying jatuh kepada kondisi gangguan kesehatan jiwa serta kuratif dan rehabilitatif bagi anak korban bullying yang sudah mengalami gangguan kesehatan jiwa. Semua upaya di atas dilaksanakan secara simultan oleh Pemerintah, Pemerintah Daerah, Masyarakat, Keluarga, dan Orang Tua. Integrasi semua komponen perlindungan hukum di atas diharapkan dapat menekan angka kejadian bullying terhadap anak dan akhirnya juga dapat menekan luarannya yaitu gangguan kesehatan jiwa.Kata kunci: Perlindungan hukum anak, Bullying, Gangguan Kesehatan Jiwa